ANALISIS MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2018 - 2021 (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI tahun 2018-2021) - Eviana, Eva; Violinda, Qristin; Indiworo , Hawik Ervina (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
This research was conducted with the aim of knowing the effect of the independent variables on the dependent variable. The independent variables used in this study are Corporate Social Responsibility and Financial Leverage. While the dependent variable in this study is Earnings Management. The data used in this study were obtained from published financial reports of manufacturing companies issued by the Indonesia Stock Exchange (IDX) for the period 2018 to 2021. The sampling technique used in this study was purposive sampling involving 30 manufacturing companies with certain criteria. The data analysis technique in this research uses multiple linear regression analysis.